Anatomical challenge: a rare coexistence of caecal cancer and isolated duodenal malrotation. Issue 10 (19th October 2022) - Sekioka, Akinori; Tsuboi, Kunihiko; Shono, Yoko; Adachi, Yukito
Abstract : Intestinal malrotation is a congenital anomaly, treated mostly during childhood. A small number of cases are incidentally found in adulthood, during operation for other abdominal diseases, such as colon cancer. Here, we present a case of caecal cancer with isolated duodenal malrotation, a subtype of intestinal malrotation, discovered incidentally during the operation for the cancer. Although the anatomical abnormality made the operation more complicated, laparoscopic resection was safely performed with oncologically adequate lymphadenectomy, owing to intraoperative confirmation of anatomy and careful dissection.